El dilema de los precios predatorios: estrategias, teorías y problemas. Un análisis del Derecho de la competencia de la Unión Europea y Antitrust (Tema Central) - Pozo Vintimilla, Patricio Francisco (2016)
Predatory prices represent one of the most studied and complex anticompetitive practices of the competition law. For decade’s universities and courts around the world have tried to establish a test to verify their effectively occurrence. Nowadays, it doesn’t exist one central proof that demonstrates with clarity, when an agent commits predatory pricing or generates a benefit to the market. In principle, the predatory prices can only exist in atomized markets (oligopoly or monopoly), it is applied by economic agents with a dominant position that have the economic capacity to assume the market share of the eliminated competitors, and operate in a market with high entry barriers. All these elements reveals that predatory pricing is a multifaceted phenomenon, making it complex to prove its existence.